PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMEN (TGT) MELALUI MEDIA FLASHCARD PADA PEMBELAJARAN BAHASA INDONESIA KELAS 2 SD - Dian Wulansari; Feri Faila Sufa; Elinda Rizkasari (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
This study aims to determine the effectiveness of the Teams Games Tournament (TGT) cooperative learning model combined with flashcards in improving Indonesian language learning outcomes among second-grade students at SDN Kleco 1 Surakarta. The approach used was quantitative, with a pre-experimental method and a One-Group Pretest-Posttest research design. All 112 second-grade students served as the population in this study, while class IId, consisting of 28 students, served as the sample, using a non-probability sampling technique. Data collection was conducted through several methods, such as observation, interviews, tests, and documentation. Furthermore, the data were analyzed using a normality test and a Paired Sample T-test for hypotheses. The results showed a significant change in Indonesian language learning outcomes after the use of flashcards. This is evident from the comparison of pretest and posttest scores, where the Paired Sample T-test yielded a significance value (2-tailed) of 0.000, which is less than α (0.05). This means there was a significant difference between the scores before and after the treatment. The average student pretest score of 50.71 increased to 79.10 in the posttest. This increase indicates that learning using flashcards positively impacts students' understanding of Indonesian. Based on these findings, it can be concluded that the TGT cooperative learning model supported by flashcards positively contributes to improving student learning outcomes in grade II of SDN Kleco 1 Surakarta.